International consensus classification of myeloid neoplasms and acute leukemias: integrating morphologic, clinical, and genomic data : special report - Arber, Daniel A.; Orazi, Attilio; Hasserjian, Robert P.; Borowitz, Michael J.; Calvo, Katherine R.; Kvasnicka, Hans-Michael; Wang, Sa A.; Bagg, Adam; Barbui, Tiziano; Branford, Susan; Bueso-Ramos, Carlos E.; Cortes, Jorge E.; et al. (Blood, 2022)
The classification of myeloid neoplasms and acute leukemias was last updated in 2016 within a collaboration between the World Health Organization (WHO), the Society for Hematopathology, and the European Association for Haematopathology. This collaboration was primarily based on input from a clinical advisory committees (CACs) composed of pathologists, hematologists, oncologists, geneticists, and bioinformaticians from around the world. The recent advances in our understanding of the biology of hematologic malignancies, the experience with the use of the 2016 WHO classification in clinical practice, and the results of clinical trials have indicated the need for further revising and updating the classification. As a continuation of this CAC-based process, the authors, a group with expertise in the clinical, pathologic, and genetic aspects of these disorders, developed the International Consensus Classification (ICC) of myeloid neoplasms and acute leukemias. Using a multiparameter approach, the main objective of the consensus process was the definition of real disease entities, including the introduction of new entities and refined criteria for existing diagnostic categories, based on accumulated data. The ICC is aimed at facilitating diagnosis and prognostication of these neoplasms, improving treatment of affected patients, and allowing the design of innovative clinical trials.
Online verfügbar: 1 July 2022, Artikelversion: 15 September 2022
Die Online-Version dieses Artikels enthält eine Datenergänzung
Gesehen am 18.09.2023